Anti‐ORAI1 antibody DS‐2741a, a specific CRAC channel blocker, shows ideal therapeutic profiles for allergic disease via suppression of aberrant T‐cell and mast cell activation. Issue 8 (8th July 2020) - Aki, Anri; Tanaka, Kento; Nagaoka, Nobumi; Kimura, Takako; Baba, Daichi; Onodera, Yoshikuni; Wada, Teiji; Maeda, Hiroaki; Nakanishi, Toshiyuki; Agatsuma, Toshinori; Komai, Tomoaki
Abstract: ORAI1 constitutes the pore‐forming subunit of the calcium release‐activated calcium (CRAC) channel, which is responsible for store‐operated calcium entry into lymphocytes. It is known that ORAI1 is essential for the activation of T cells and mast cells and is considered to be a potent therapeutic target for autoimmune and allergic diseases. Here, we obtained a new humanized antibody, DS‐2741a, that inhibits ORAI1 function. DS‐2741a bound to human‐ORAI1 with high affinity and without cross‐reactivity to rodent Orai1. DS‐2741a demonstrated suppression of CRAC‐mediated human and mouse T‐cell activation and mast cell degranulation in human ORAI1 knock‐in mice. Furthermore, DS‐2741a ameliorated house dust mite antigen‐induced dermatitis in the human ORAI1 knock‐in mouse. Taken together, DS‐2741a inhibited T‐cell and mast cell functions, thus improving skin inflammation in animal models of atopic dermatitis and reinforcing the need for investigation of DS‐2741a for the treatment of allergic diseases in a clinical setting.